Pengaruh Sumber Pembiayaan Desentralisasi Fiskal terhadap Tingkat Kemiskinan - Yunaida, Ari; Wiranata Saputra, Angga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the effect of fiscal decentralization financing sources on poverty levels. This study covers areas in Jambi Province using secondary time series data for the period 2007-2016. This study uses Multiple Regression Analysis. Fiscal decentralization financing sources of local revenue and balancing funds do not have a significant positive effect on poverty levels in Jambi Province, while other legitimate incomes have a positive and significant effect in Jambi Province from 2007-2016. The effect of fiscal decentralization financing sources (PAD, DP, PL) on poverty levels in Jambi Province is 80.2%, while the remaining 19.8% is influenced by other factors not included in this study. And there is a strong relationship between fiscal decentralization and poverty levels of 89.6%.